Pemberdayaan Masyarakat Sekitar Kampus Kelurahan Lere Melalui Pelatihan Pembuatan Nugget Ikan - Asrawaty, Asrawaty; If?all, If?all (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Today's urban society is inclined to buy practical, ready-to-cook food and ready to eat. Ready of cook means thatit takes less time to prepare food. One form of food that is ready to cook is a nugget. Fish nuggets are very easy to processand the raw material of tuna is easily obtained in Lere urban village. aims to empower communities around the campuswith a commercial business orientation and accelerated the development, coaching, creati on of network marketing results,continuously. Using Community Education methods with Participatory Rural Appraisal (PRA/ RRA), training methods,demonstration experiments, and coaching and evaluation of small business partner groups. The demonstrationdemonstration demonstration demplot was conducted with the introduction of technology covering fish nugget processingtechnology. The result of this training activity is the Improvement of ability in running the partner business through thetraining activity that is held. Increasing the capability and income of community partners activities with the existence offish processing technology into nugget is one of food diversification and food preservation